THEORETICAL PRINCIPLES FOR DETERMINING THE VALUE OF THE LIFE CYCLE OF THE TRACTION ROLLING STOCK - Kalabuhin, Yu. Ye. (Science and Transport Progress, 2008)
In the article the basic theoretical statements of determination of cost of life cycle for the tractive rolling stock as a prerequisite of feasibility study of its update in the modern conditions of economic development are presented.